IMPLEMENTASI MEDIA POP-UP BOOK PADA MATERI KERAGAMAN BUDAYA UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD: SYSTEMATIC LITERATURE REVIEW - Tri Febrianto, Priyono; Agustina, Rufaydah; Novita, Tri; Aidah Fatin, Rifka; Nur Choyyina, Avin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social Studies (IPS) learning in fourth grade elementary schools plays a crucial role in building students' understanding of social and cultural phenomena, including Indonesia's cultural diversity. This material is often presented textually, making it difficult for students to grasp concepts in depth and reducing active engagement and learning outcomes. This study aims to analyze the implementation of pop-up book media in social studies learning on cultural diversity and its impact on student learning outcomes. The method used is a Systematic Literature Review (SLR) by analyzing approximately 45 scientific articles published between 2022 and 2026. Data were analyzed thematically to identify the characteristics of media implementation, its influence on learning outcomes, and factors supporting successful media use. The results of the study indicate that pop-up book media is effective in increasing students' conceptual understanding, active engagement, and learning motivation. This media presents material in a concrete and visual manner, allows for the integration of local cultural values, and supports the implementation of cooperative learning strategies, problem-based learning, and discovery learning. The success of implementation is influenced by student interest and motivation, media flexibility, and teacher competence in designing and integrating media into learning. The main obstacles are related to limited teacher skills and facilities/infrastructure. In conclusion, pop-up books are an innovative, interactive, and contextual learning alternative for improving student learning outcomes and understanding of cultural diversity. Further research is needed to expand its scope and evaluate its long-term effects.